Single‐institution retrospective review of patients with recurrent glioblastoma treated with bevacizumab in clinical practice. Issue 4 (13th February 2019) - Desjardins, Annick; Herndon, James E.; McSherry, Frances; Ravelo, Arliene; Lipp, Eric S.; Healy, Patrick; Peters, Katherine B.; Sampson, John H.; Randazzo, Dina; Sommer, Nicolas; Friedman, Allan H.; Friedman, Henry S.
Abstract: Background and aims: This retrospective review of patients with recurrent glioblastoma treated at the Preston Robert Tisch Brain Tumor Center investigated treatment patterns, survival, and safety with bevacizumab in a real‐world setting. Methods: Adult patients with glioblastoma who initiated bevacizumab at disease progression between January 1, 2009, and May 14, 2012, were included. A Kaplan‐Meier estimator was used to describe overall survival (OS), progression‐free survival (PFS), and time to greater than or equal to 20% reduction in Karnofsky Performance Status (KPS). The effect of baseline demographic and clinical factors on survival was examined using a Cox proportional hazards model. Adverse event (AE) data were collected. Results: Seventy‐four patients, with a median age of 59 years, were included in this cohort. Between bevacizumab initiation and first failure, defined as the first disease progression after bevacizumab initiation, biweekly bevacizumab and bevacizumab/irinotecan were the most frequently prescribed regimens. Median duration of bevacizumab treatment until failure was 6.4 months (range, 0.5‐58.7). Median OS and PFS from bevacizumab initiation were 11.1 months (95% confidence interval [CI], 7.3‐13.4) and 6.4 months (95% CI, 3.9‐8.5), respectively. Median time to greater than or equal to 20% reduction in KPS was 29.3 months (95% CI, 13.8‐∞). Lack of corticosteroid usage at the start of bevacizumab therapy was associated with both longer OS and PFS, with a median OS of 13.2 months (95% CI, 8.6‐16.6) in patients who did not initially require corticosteroids versus 7.2 months (95% CI, 4.8‐12.5) in those who did ( P  = 0.0382, log‐rank), while median PFS values were 8.6 months (95% CI, 4.6‐9.7) and 3.7 months (95% CI, 2.7‐6.6), respectively ( P  = 0.0243, log‐rank). Treatment failure occurred in 70 patients; 47 of whom received salvage therapy, and most frequently bevacizumab/carboplatin (7/47; 14.9%). Thirteen patients (18%) experienced a grade 3 AE of special interest for bevacizumab. Conclusions: Treatment patterns and outcomes for patients with recurrent glioblastoma receiving bevacizumab in a real‐world setting were comparable with those reported in prospective clinical trials.